English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

g(x) = (18x + -36)/30

A g^-1(x) = (5/30)x + 2
B g^-1(x) = (5/3)x - 2
C g^-1(x) = (3/5)x + 2/5
D g^-1(x) = 3x + 2
E g^-1(x) = (5/3)x + 2
F g^-1(x) = (5/30)x + 1/15

2007-05-31 06:44:19 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

To clarify my thinking, I prefer to write g(x) as y.
y = (18x + -36)/30

To find the inverse function, replace y with x and x with y:
x = (18y + -36)/30
Then solve this for y:
30x = 18y - 36
30x + 36 = 18y
y = (30x + 36)/18
y = (5/3)x + 2

The inverse function is g^-1(x) = (5/3)x + 2
In other words, the correct answer is E.

Hope that helps!

2007-05-31 07:00:29 · answer #1 · answered by Bramblyspam 7 · 0 0

E

2007-05-31 13:52:27 · answer #2 · answered by Stop Sine 3 · 0 0

fedest.com, questions and answers